Design and Development of an Automatic Watering System Based on Bash Shell with OpenWRT Platform on Chili Plants - Son’Aniy, Irham; Sugiantoro, Bambang (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
Indonesia is an agrarian country. Because of the wide agriculture area, Indonesia became the exporter country in agriculture sector. Nowadays, the developments in every fields are always increasing. One of those field is technology. Technology should give some contributions which can develop the agriculture field. One of the contribution that can be done is automatic watering system on chili, so it become easier for the farmers to control the chili. The automatic watering system use internet technology to control a device from distance. This chili’s automatic watering system based on bash shell with openWRT platform. This system was made to help farmers watering the chili automatically. The methods that used in this system can be based on the soil’s moisture, time, or manual. Soil’s moisture based method used soil moisture, that tool can measure the ground’s moisture and automatically send order to the device. This system can reduce delays of the chili’s daily treatment, so the chili’s production will be increasing. This system development used SLDC (Systems Development Life Cycle) method. Automatic watering system with openWRT platform can help farmers in watering and controlling chili. The system can perform the function of automatic watering feature and functionality can run well.